Locked-flavylium fluorescent dyes with tunable emission wavelengths based on intramolecular charge transfer for multi-color ratiometric fluorescence imaging. Issue 32 (23rd March 2015) - Chen, Hua; Lin, Weiying; Jiang, Wenqing; Dong, Baoli; Cui, Haijun; Tang, Yonghe
Abstract : A new class of locked-flavylium fluorophores with tunable emission wavelengths based on intramolecular charge transfer were designed, synthesized, and evaluated. Abstract : A new class of locked-flavylium fluorophores with tunable emission wavelengths based on intramolecular charge transfer were designed, synthesized, and evaluated. The optical studies indicate that sensorLF3 can display an intriguing character, fluorescence ratiometric response in three channels by tuning the ICT efficiencies.